Din eğitimi açısından hikmet kavramı - Batman, Elif (My University, 2016)
DİN EĞİTİMİ AÇISINDAN HİKMET KAVRAMI Hikmet kavramı, İslam düşüncesinde en geniş anlamda yer tutan kavramlardan biridir. Bu geniş alan içinde hikmetin farklı anlaşılma biçimlerini görmek mümkündür. Ancak bütün hikmet anlayışları, eşyanın hakikatini bilmek ve bu bilmenin gereğine uygun şekilde davranmak temeline dayanmaktadır. Böylesi bir bilme-eyleme birlikteliği insanı kötülükten alıkoyup iyi olana yönelteceği için de, İslam düşüncesinde insanı kötülükten alıkoyup iyi olana yönlendiren her şey, hikmetin geniş kapsamı içinde düşünülmüştür. Din eğitiminin felsefî arka planına bir katkı sağlamayı umduğumuz bu çalışmada, hikmet kavramının din eğitimi açısından anlamı sorgulanmaktadır. Bu sorgulamayı yapabilmek için İslam düşüncesinin hikmete dair mülahazalarından yola çıkılmış ve Ahmed Yesevî’nin Divan-ı Hikmet adlı eseri, hikmeti okuyabileceğimiz bir örnek olarak seçilmiştir. Bütün bu verilerden hareketle din eğitimi açısından hikmetin, insanın kendisini ve hayatı sözle, ahlakla, düşünceyle ve hal ile anlaması olarak yorumlanabileceği düşünülmektedir. kmet, Ahmed Yesevî, Divan-ı Hikmet.

THE CONCEPT OF WISDOM IN TERMS OF RELIGIOUS EDUCATION The concept of wisdom (hikmah) is one of the well-known issues in Islamic philosophical thought. For this reason, it is possible to see different interpretations of hikmah. Yet, all these interpretations depend on the law of the instrument and behave according to this rule. Since this kind of attitude prevent people from misbehaving and lead them to the good one, the thing which prevent people from misbehaving and lead them to the good one in Islamic philosophy is thought according to the concept of hikmah. This study aims to contribute philosophical background of the religious education, within this context the meaning of concept of hikmah in terms of religious education is being inquired. In order to make this happen, the understanding of hikmah in Islamic thought has been regarded as the starting point and Ahmed Yesevi’s influential study ‘Diwanı Hikmet’ chosen as an example that we can deduce the meaning of hikmah. Depending on all these data, in this study, the concept of hikmah is thought as the human’s comprehension of himself and life through the word, moral principles, thought and manner in terms of religious education. Key Words : Religious Education, Wisdom, Hikmah, Ahmed Yassawî, Diwani Hikmet ABSTRACT The aim of this study was to evaluate the diagnostic performances of the diffusion tensor (DT) imaging parameters in the differentiation of malignant from benign tumors, and to investigate the variations in DTI parameters according to the immunohistochemical biomarkers and their surrogates of the intrinsic subtypes in early breast cancer patients, and to compare them with ADC values of standard diffusion-weighted (DW) imaging. The prospective study included 85 patients with 92 enhancing breast lesions. DT imaging was performed during the breast MRI at 3.0 T. DT imaging parameters including eigenvalues, λ1-λ3, λ1-λ2, λ2-λ3, mean diffusivity (MD), radial diffusivity (RD), fractional anisotropy (FA), relative anisotropy (RA), and geodesic anisotropy (GA) were measured in each lesion. DT imaging parameters were compared between malign, benign lesions. The ADC values compared with DT imaging parameters. In malign lesions DT imaging parameters were correlated with estrogen receptor (ER), human epidermal growth factor receptor 2 (HER-2) and Ki-67 status and immunohistochemical surrogates of the intrinsic subtypes. MD, RD, λ1, λ2, and λ3 values were significantly lower in malign lesions than benign lesions and malign lesions exhibited significantly higher values of FA, RA and GA (p < 0.001). In ER-positive breast cancer RD, λ2, and λ3 values were lower than ER-negative breast cancer with significant difference (p < 0.05). On the contrary FA, RA and GA values were higher in ER-positive breast cancer (p < 0.05). Ki-67 expression showed statistically significant, negative correlation with FA, RA, GA, λ1-λ3 and λ1-λ2 values (p < 0.05). In conclusion, this study showed that DT imaging provides useful diagnostic information to differentiate malignant and benign breast lesions. Moreover, various DT imaging parameters showed correlation with ER and Ki-67 status. ffusion tensor imaging, fractional anisotropy, breast cancer, estrogen receptor, Ki-67
Keywords: Din; Din eğitimi; Eğitim ve öğretim (İlk); Türkiye